Medical treatment for dry eye in patients with keratoconus after corneal cross-linking - I.A. Bubnova; G.B. Egorova; V.V. Averich; T.S. Mitichkina (РМЖ "Клиническая офтальмология")
I.A. Bubnova, G.B. Egorova, V.V. Averich, T.S. Mitichkina Scientific Research Institute of Eye Diseases, Moscow, Russian Federation Aim: to assess the changes in precorneal tear film in patients with keratoconus after corneal cross-linking (CXL). Patients and Methods: 16 patients (17 eyes) were enrolled. Keratoconus stage 1 was diagnosed in 4 eyes, keratoconus stage 2 in 12 eyes, and keratoconus stage 3 in 2 eyes. All patients underwent ocular examination before and in 1 week and 1 month after CXL. Tear film was assessed by slit lamp examination, Norn’s test (tear break-up time), Schirmer’s test (total tear production), Jones test (basic tear production), and tearscopy. Results: instability of precorneal tear film was revealed in 72% of patients before CXL as demonstrated by functional tests. Total and basic tear production was below normal ranges in 45% and 50%, respectively. In a week after CXL, complete corneal epithelization without any signs of staining with fluorescein was observed in a total of 16 patients. Functional tests have demonstrated that significant changes are observed in Norn’s test only (39% increase from the baseline). In a month, tear film break-up time significantly (by 2.5 times) increased as compared with the baseline (p=0.02). Total and basic tear production also improved by 3.7% in a week (p=0.81) and by 11% in a month (p=0.86). Tear film lipid layer tended to restore in a month after CXL. Conclusion: our findings demonstrate insignificant effect of CXL on tear production. However, long-term exposure to blepharostat may result in lipid layer thinning and impaired tear film homeostasis as demonstrated  by tearscopy. Postoperative tear substitutes and reparative therapy result in the significant improvement of tear film stability. Keywords: dry eye, corneal cross-linking, keratoconus, tear film, tear substitutes. For citation: Bubnova I.A., Egorova G.B., Averich V.V., Mitichkina T.S. Medical treatment for dry eye in patients with keratoconus after corneal cross-linking. Russian Journal of Clinical Ophthalmology. 2020;20(2):67–71. DOI: 10.32364/2311-7729-2020-20-2-67-71.